Senior Lecturers’ Narrative Experience in Traversing the Transformations of Curriculum: 1994 Curriculum to Merdeka Curriculum - Nurbani, Armelia Nungki; Setiawan, Rahmat (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Curriculum transformations bring its own challenges for educators, especially at the university level, because universities become the main axis in curriculum testing and practice. The theoretical framework used in this research is the concepts of Curriculum, Narrative Inquiry, and also Teaching Experience. The approach in this research is narrative, the data in this research are fragmented statements taken from interviews. The interviewees are the data sources and they are 2 senior lecturers at a university in Surabaya. The 2 lecturers have been teaching for more than 25 years so they are valid to be used as sources because they have gone through various curriculum transformations since 1994 to 2024. The data collection technique in this research is interview and the type of the interview is nonstructured interview which serves to explore the experience of the interviewees. The type of analysis technique in this research is thematic analysis which serves to divide the results of the analysis into themes of findings. From the results of the research, it can be found that the challenges of the lecturers are 3 things: understanding, adjustment, and implementation. The senior lecturers see this change as a challenge that encourages them to learn and develop.